Balla and Depero in Architecture - Alberto Sposito (Agathón)
Giacomo Balla and Fortunato Depero mainly practiced pictorial and decorative art oriented for the industrial design field. On various occasions and in a different way the two artists worked in the field of architecture. This essay focuses on these interventions.